Acute Kidney Injury in Critically Ill Children and Subsequent Chronic Kidney Disease. Issue 1 (October 2019) - Hessey, Erin; Perreault, Sylvie; Dorais, Marc; Roy, Louise; Zappitelli, Michael
Background: The progression from acute kidney injury (AKI) to chronic kidney disease (CKD) is not well understood in children. Objectives: We aimed to develop a pediatric CKD definition using administrative data and use it to evaluate the association between AKI in critically ill children and CKD 5 years after hospital discharge. Design: Retrospective cohort study using chart collection and administrative data. Setting: Two-center study in Montreal, Canada. Patients: Children (≤18 years old) admitted to two pediatric intensive care units (ICUs) between 2003 and 2005. We a priori excluded patients with end-stage renal disease or no health care number. Only the first admission during the study period was included. We excluded patients who could not be linked to administrative data, did not survive hospitalization, or had preexisting renal disease. Measurements: Acute kidney injury was defined using Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Patients were defined as having CKD 5 years post-discharge if they had ≥1 CKD diagnostic code or ≥1 CKD-specific medication prescription. Methods: Chart data used to define the exposure (AKI) were merged with provincial administrative data used to define the outcome (CKD). Cox regression was used to evaluate the AKI-CKD association. Results: A total of 2235 (56% male) patients were included, and the median admission age was 3.7 years. A total of 464 (21%) patients developed AKI during pediatric ICU admission. At 5 years post-discharge, 43 (2%) patients had a CKD diagnosis. Patients with both stage 1 and stage 2-3 AKI had increased risk of a CKD diagnosis, with the adjusted hazard ratios (95% confidence intervals) of 2.2 (1.1-4.5) and 2.5 (1.1-5.7), respectively ( P < .001). Limitations: Results may not be generalizable to non-ICU patients. We were not able to control for post-discharge variables; future research should try to explore these additional potential risk factors further. Conclusions: Acute kidney injury is associated with 5-year post-discharge CKD diagnosis defined by administrative health care data.